Pengaruh Latihan Shuttle Run dan Zig-Zag Terhadap Kemampuan Dribbling Sepak Bola Pada Kegiatan Ekstrakurikuler Siswa di SMA Negeri 18 Palembang (International Forum of Researchers and Lecturers, 2024)
The problem in this research is whether there is an effect of shuttle run training and zig-zag training methods on soccer dribbling skills in extracurricular students at SMA 18 Palembang. The aim of this study is to determine the different effects of shuttle run and zig-zag drills on dribbling skills in students participating in extracurricular activities. This research uses a quantitative approach with a pre-experimental design in the form of a two-group pretest and posttest design. The data collection techniques used in this research include observation, documentation, and tests. The data analysis techniques applied are normality test, homogeneity test, and hypothesis testing. Based on the research results, the T-test value for the shuttle run training experiment group is 8.422, and for the zig-zag training experiment group, it is 5.606. The T-test values from both variables' pretest and posttest results conclude that there is an effect of shuttle run and zig-zag training on soccer dribbling skills in extracurricular activities at SMA Negeri 18 Palembang. It can be observed that the average time for shuttle run training before treatment was 15.10 seconds and after treatment was 14.07 seconds, while for zig-zag training, the average time before treatment was 14.47 seconds and after treatment was 13.55 seconds. It can be concluded that zig-zag training has a more significant effect on soccer dribbling skills than shuttle run training in extracurricular activities at SMA 18 Palembang.